2021
DOI: 10.1186/s12877-020-01983-0
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation and preliminary psychometric properties of three self-stigma outcome measures for people living with dementia

Abstract: Background A diagnosis of dementia presents individuals with both social and psychological challenges but research on self-stigma in dementia has been largely confined to qualitative approaches due to a lack of robust outcome measures that assess change. The Stigma Impact Scale (SIS) is the most commonly used measure of self-stigma in dementia but its suitability as a tool to assess change in a UK population is unclear. Thus, the aim of this study was to identify, adapt and evaluate the accepta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 49 publications
3
13
0
Order By: Relevance
“…Analyses indicate that the stigma measures are reliable and valid for use in a Dutch population with high internal consistencies for most (sub)scales, as has previously been found for English versions of these scales (Bhatt et al, 2021). The only scale not showing adequate internal consistency was the internalised shame subscale of the Stigma Impact Scale, in line with previous studies with people living with dementia (Bhatt et al, 2021;Lion et al, 2020), perhaps partly due to the small number of items (n = 3).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Analyses indicate that the stigma measures are reliable and valid for use in a Dutch population with high internal consistencies for most (sub)scales, as has previously been found for English versions of these scales (Bhatt et al, 2021). The only scale not showing adequate internal consistency was the internalised shame subscale of the Stigma Impact Scale, in line with previous studies with people living with dementia (Bhatt et al, 2021;Lion et al, 2020), perhaps partly due to the small number of items (n = 3).…”
Section: Discussionsupporting
confidence: 84%
“…Analyses indicate that the stigma measures are reliable and valid for use in a Dutch population with high internal consistencies for most (sub)scales, as has previously been found for English versions of these scales (Bhatt et al, 2021). The only scale not showing adequate internal consistency was the internalised shame subscale of the Stigma Impact Scale, in line with previous studies with people living with dementia (Bhatt et al, 2021;Lion et al, 2020), perhaps partly due to the small number of items (n = 3). The study showed that Dutch participants who reported more severe stigma impact or consequences, i.e., social rejection, internalised shame, and social isolation, as well as perceived stigma-related harm and secrecy also reported lower self-esteem, whereas greater resources to cope with stigma were associated with higher self-esteem.…”
Section: Discussionsupporting
confidence: 84%
“…6,7 This study is, to our knowledge, the first quantitative exploration of stigma by association, affiliate stigma and positive aspects of caregiving with family carers of people living with dementia in the UK. This study adds to the notion of the 'double effect' of dementia on experiences of stigma, where people living with dementia experience stigma 14 and the majority of their carers also experience stigma. Our results show that carers endorsed stigma by association, suggesting they were aware that others viewed or treated them in a stigmatising fashion; however, the lack of endorsement of affiliate stigma constructs (e.g.…”
Section: Discussionmentioning
confidence: 82%
“…Previous literature has documented an inverse relationship between self-esteem and stigma in dementia, HIV/AIDs and cancer. [12][13][14] Therefore, it was hypothesised that stigma by association and affiliate stigma would be negatively correlated with self-esteem, whereas the positive aspects of caregiving subscale would be positively correlated.…”
Section: Rosenberg Self-esteem Scalementioning
confidence: 99%
“…According to a study conducted by Kim and Jung (2015), 208 Koreans aged 65 and over perceived dementia as a stigma, and the score was 53 out of 100. A study conducted by Bhatt et al (2021) have reported that older adults with dementia have been found to be at risk of self-stigma. Another study conducted by Yang et al (2021) investigated 372 community-dwelling adults in Shanghai aged 60 and older.…”
Section: Factor Iii: Dementia Is a National Responsibility (National-...mentioning
confidence: 99%